From creation to redemption progressive approaches to Midrash - Nelson, David W.; Ulmer, Rivka 1951- (Judaism in context, 2017)
"This volume contains select papers presented in the sessions of the Midrash Section at the 2015 and 2016 annual meetings of the Society of Biblical Literature. The contributors of these chapters not only define and demarcate, but also employ and apply, methodological approaches to the study of midrash that range from fundamental and foundational to forward-thinking and progressive, e.g., traditional critical-historical approaches, literary, topical and atomistic approaches, comparative and theological approaches, and feminist approaches. The result is a volume distinguished by its simultaneous attention to the scholarly past, present, and future of the ever-emerging and unfolding field of study devoted to the biblical interpretation of the earliest rabbis"...